Soft gold nanowire sponges for strain-insensitive conductors, wearable energy storage and catalytic converters. Issue 42 (25th October 2021) - Lin, Fenge; Wang, Kaixuan; An, Tiance; Zhu, Bowen; Ling, Yunzhi; Gong, Shu; Liu, Siyuan; Cheng, Wenlong
Abstract : We present a solution-based strategy to fabricate a gold nanowire sponge. This gold sponge is a multifunctional smart material, which can serve as a strain-insensitive conductor, a deformable supercapacitor and a recyclable 3D porous catalyst. Abstract : Electronics is evolving from rigid, flexible to ultimate stretchable electronics, in which active optoelectronic materials are required to be deposited onto or embedded into elastomeric materials. We have recently demonstrated a powerful solution-based electroless gold coating technology, which enables the growth of enokitake-like gold nanowires on two-dimensional elastomeric sheets and one-dimensional fibers for a wide range of applications in wearable bioelectronics. Here, we show that such an elastomeric gold coating technology can be extended to three-dimensional (3D) elastomeric sponges. We have successfully grown vertically-aligned enokitake-like gold nanowires (v-AuNWs) uniformly throughout 3D sponge skeletons, leading to a highly conductive sponge with a conductivity of up to about 1500 S m −1 . This, in conjunction with embedment of Ecoflex into porous v-AuNW sponge, led to a strain-insensitive conductor that only changed about 17.3% in resistance under 50% strain, and 83.3% in resistance under 100% strain. The conductor could be stretched up to ∼340% strain before losing its conductivity. Furthermore, the strain-insensitive sponge conductors were used as electrodes to fabricate elastic supercapacitors, which could retain 102% and 99% of initial capacitance under 50% compression strain and 180° bending, respectively. In addition, our gold sponge was also catalytically active, and could serve as a recyclable 3D porous catalyst (achieving 90% conversion efficiency even after 10 cycles of 4-nitrophenol reduction reaction). The results presented here demonstrate a simple yet efficient wet chemical approach to a multifunctional sponge for applications in stretchable electronics, wearable energy devices and catalysis.